Eksekutabilitas Penetapan Penundaan Pelaksanaan Keputusan Tata Usaha Negara - Asmuni (Perspektif Hukum, 2016)
The research discusses the issues that emerge from executing the postponement stipulation of the administrative decision implementation and the concept of regulating the execution of postponement stipulation of the administrative decision implementation that can protect the interests of litigants. The research constitutes a normatively legal research. The used approach is the conceptual and statute approaches. The result of the research shows that postponing the administrative decision implementation makes applicable power of the sued administrative decision suspended temporarily; postponing the administrative decision implementation makes legal circumstances back to the first position, prior to the administrative decision disputed; and postponing the administrative decision implementation restricts to apply the principle of the legal presumption. Due to the influence of the postponement stipulation of the administrative decision implementation, it is necessary to put philosophically and theoretically and juridically legal reasons on the judge decision. The public interest reason is not required, because the administrative decision on the public interest has not become the State Administrative Court authority since the first time. The legal instruments used to postpone the execution of the administrative decision is an interlocutory decision not stipulation.